Land use and land cover changes and Soil erosion in Yezat Watershed, North Western Ethiopia - Tadesse, Lemlem; Suryabhagavan, K.V.; Sridhar, G.; Legesse, Gizachew (International Soil and Water Conservation Research, 2017)
Soil erosion affects land qualities and water resources. This problem is severe in Ethiopia due to its topographic features. The present research was aimed to estimate spatiotemporal changes in land-use/land-cover pattern and soil erosion in the Yezat watershed in Ethiopia. This study was carried out by using landsat imageries of 2001, 2010 and 2015. Images were classified into categories using supervised classification by maximum likelihood algorithm. They were also classified into different biomass levels by using Normalized Difference Vegetation Index (NDVI) analysis. Revised Universal Soil Loss Equation modeling was applied in a GIS environment to quantify the potential soil erosion risk. The area under grassland, woodland and homesteads have increased by 610.69 (4%), 101.69 (0.67%) and 126.6 ha (0.83%) during 2001–2015. The extent of cultivated land and shrub/bushland was reduced by 323.43(0.02%) and 515.44 ha (3.41%), respectively, during the same period. The vegetation cover in the watershed decreased by 91% during 2001–2010, and increased by 88% during 2010–2015. Increase of NDVI values indicates better ground cover due to implementation of integrated watershed development program in the region. The estimated annual soil losses were 7.2tha−1yr−1 in 2001, 7.7t ha−1yr−1in 2010 and 4.8tha−1yr−1in 2015. Management interventions are necessary to improve the status and utilization of watershed resources in response to sustainable land management practices for sustainable livelihood of the local people.